Investigating the Potential of Conjugated Selenium Redox Folic Acid as a Treatment for Triple Negative Breast Cancer - Soni Khandelwal; Mallory Boylan; Gilbert Kirsch; Julian E. Spallholz; Lauren S. Gollahon (MDPI AG, 2020)
Previous studies have demonstrated that redox selenium compounds arrest cancer cell viability in vitro through their pro-oxidative activity by generating superoxide (O2•−). Currently, there are no efficacious treatment options for women with Triple Negative Breast Cancer (TNBC). However, the association between the over-expression of the Folate Receptor Alpha (FRA) in TNBC and other cancer cells, has led to the possibility that TNBCs might be treated by targeting the FRA with redox selenium covalent Folic Acid conjugates. The present study reports the synthesis of the redox active vitamer, Selenofolate, generating superoxide. Superoxide (O2•−) catalytic generation by Selenofolate was assessed by an in vitro chemiluminescence (CL) assay and by a Dihydroethidium (DHE) in vivo assay. Cytotoxicity of Selenofolate was assessed against the TNBC cell line MDA-MB-468 and an immortalized, mammary epithelial cell line, HME50-5E. Cytotoxicity of Selenofolate was compared to Folic Acid and sodium selenite, in a time and dose dependent manner. Selenofolate and selenite treatments resulted in greater inhibition of MDA-MB-468 cell proliferation than HME50-5E as evaluated by Trypan Blue exclusion, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) metabolic assay and Annexin V apoptosis assays. Folate receptor alpha (FRA) protein expression was assessed by Western blotting, with the experimental results showing that redox active Selenofolate and selenite, but not Folic Acid, was cytotoxic to MDA-MB-468 cells in vitro, suggesting a possible clinical option for treating TNBC and other cancers over-expressing FRA.